PENGARUH BUDAYA ORGANISASI DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN PADA PT. DIAMOND PRIMA INDONESIA KOTA TANGERANG - Submission JORAPI; Septika Asri; Priehadi Dhasa Eka (Journal of Research and Publication Innovation, 2025)
This study aims to determine the effect partially or simultaneously of Organizational Culture and Work Motivation on Employee Performance at PT. Diamond Prima Indonesia Tangerang city. This type of research is quantitative. The sampling technique used saturated sampling, and a sample of 70 respondents was obtained. The data collection used was a questionnaire, the data analysis technique used was data validity test, reliability test, classical assumption test, multiple linear regression test, and hypothesis testing. The results obtained in the study based on the t test on organizational culture variable tcount 4.195 > ttable 1.995 with a significant level of 0.000 <0.05 means that organizational culture (X1) has a partial and significant effect on Employee Performance (Y) and Work Motivation variables (X2) tcount of 4.729 and ttable 1.995 with a significant level of 0.000 <0.05 means that Work Motivation (X2) has a partial and significant effect on Employee Performance (Y). Meanwhile, based on the results of the F test, it was found that the Fcount value was 72.599 > Ftable 3,13 with a significant level of 0,00 <0.05, it can be concluded that Organizational Culture (X1) and Work Motivation (X2) simultaneously have an effect on and are significant on Employee Performance (Y) at PT. Diamond Prima Indonesia Tangerang city. With a coefficient of determination of 67,5.% while the rest (100 –67,5%) = 32,5% is influenced by other factors.